1 answer:
Answer:
Rewrite
by applying exponent rule
:
![\implies (csc^2x)^2-(cot^2x)^2](https://tex.z-dn.net/?f=%5Cimplies%20%28csc%5E2x%29%5E2-%28cot%5E2x%29%5E2)
Apply difference of two squares formula
:
![\implies (csc^2x+cot^2x)(csc^2x-cot^2x)](https://tex.z-dn.net/?f=%5Cimplies%20%28csc%5E2x%2Bcot%5E2x%29%28csc%5E2x-cot%5E2x%29)
Using trig identity ![1+cot^2x=csc^2x \implies 1=csc^2x-cot^2x](https://tex.z-dn.net/?f=1%2Bcot%5E2x%3Dcsc%5E2x%20%5Cimplies%201%3Dcsc%5E2x-cot%5E2x)
![\implies (csc^2x+cot^2x)(1)](https://tex.z-dn.net/?f=%5Cimplies%20%28csc%5E2x%2Bcot%5E2x%29%281%29)
![\implies csc^2x+cot^2x](https://tex.z-dn.net/?f=%5Cimplies%20csc%5E2x%2Bcot%5E2x)
You might be interested in
Answer:
1
Step-by-step explanation:
2-1=1
Answer:
3.2
Step-by-step explanation:
11.5 - 5.1 = 6.4
6.4 ÷ 2 = 3.2
Answer:
sqrt(5)*sqrt(5)=5.
Step-by-step explanation:
Answer:
plz make brainy least and your answer is here
Not sure(this might be wrong) but “30>p”